THE EFFECTIVENESS OF INTEGRATING GASING AND DEEP LEARNING IN IMPROVING MATHEMATICS LEARNING OUTCOMES FOR ELEMENTARY SCHOOL STUDENTS - Kadek Ashadi Putra; Yusuf Tri Herlambang; Yunus Abidin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to systematically examine the application of the Gasing method integrated with a Deep Learning approach in elementary school mathematics education, focusing on its impact on students’ learning achievement. The Gasing method emphasizes deep conceptual understanding, strengthens connections among mathematical concepts, and promotes students’ critical and reflective thinking skills. Beyond improving academic performance, this approach supports meaningful learning and cognitive development throughout the instructional process. This research employs a Systematic Literature Review (SLR) methodology by analyzing 14 relevant academic articles published between 2020 and 2025, sourced from reputable databases, including Google Scholar. The SLR approach was selected for its ability to provide a comprehensive, objective, and evidence-based synthesis of existing research findings. The results indicate that the implementation of the Gasing method in elementary mathematics learning consistently has a positive effect on students’ achievement, encompassing both cognitive and affective domains. These findings highlight the significance of integrating the Gasing method with a Deep Learning approach to create engaging, reflective, and meaningful learning experiences. Therefore, this instructional approach demonstrates strong potential for wider application in primary education to enhance the quality of mathematics learning.